2011
DOI: 10.4028/www.scientific.net/amr.314-316.1287
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Implementation of a CAD/CAE Integrated System for Plastic Injection Molding

Abstract: In the plastic injection molding process, interaction between design and analysis is very intensive. However, current computer-aided systems (CAD and CAE) are realized as isolated modules. Thus, designers need to transform data models between CAD and CAE systems. Defects of many data errors and duplicated work are inevitable. This paper presents a CAD/CAE integrated system, building on top of existing CAD and CAE systems. The framework of the system is designed. A parametric integration model is established to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…However, many factors, such as simplified mathematical models, incorrect processing conditions and material property settings, mold rigidity, and machine aging may cause the simulation results to be inconsistent with the actual molding results. Consequently, Li et al [ 4 ] established a system that integrates computer‐aided design and CAE to identify product features, automatically generate meshing to reduce the differences with actual finished products, transform analysis results, and modify models to improve the efficiency of mold flow analysis. Huang et al [ 5 ] suggested that the difference between simulation and actual results mainly arises from the difference between the simulated and the actual injection speed response time.…”
Section: Introductionmentioning
confidence: 99%
“…However, many factors, such as simplified mathematical models, incorrect processing conditions and material property settings, mold rigidity, and machine aging may cause the simulation results to be inconsistent with the actual molding results. Consequently, Li et al [ 4 ] established a system that integrates computer‐aided design and CAE to identify product features, automatically generate meshing to reduce the differences with actual finished products, transform analysis results, and modify models to improve the efficiency of mold flow analysis. Huang et al [ 5 ] suggested that the difference between simulation and actual results mainly arises from the difference between the simulated and the actual injection speed response time.…”
Section: Introductionmentioning
confidence: 99%